Feasibility of Banana Chips Agroindustry Business IKM Banua Pagatta in Lolu Village Sigi Biromaru District, Sigi Regency Sulawesi Tngah - Marliyah; Irmawaty; Riskayanti (Universitas Muhammadiyah Palu, 2024)
Kepok banana chip is one of the processed banana products used as daily snack, especially for the people of Sigi Regency. It has even been marketed to several areas around Sigi Regency. The banana chips business produced by IKM Banua Pagatta has started to actively manage its business again three years ago. However, how much profit and feasibility have been obtained so far and to what extent can this business return the invested capital and what products are sold in what forms generate the highest income. The purpose of this study was to determine the level of financial feasibility of the banana chip business which was carried out from November 2022 to January 2023. The selection of respondents was carried out purposively with 2 persons, namely the owner IKM Banua Pagatta business. The data analysis method used is financial feasibility analysis, with several criteria, namely: Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR), Payback Period (PP). The results show that the Financial Feasibility of the Kepok Banana chips business of IKM Banua Pagatta used 4 calculation criteria: For production in bulk form/Kg, the NPV was Rp. 20,801,153; Net B/C of 1.22; IRR of 17.31% and PP for 2 years 2 days. As for production in the form of packaging, the NPV is 10,801,153, Net B/C is 1.10, IRR is 16.23% and PP 2 years 1 month and both of them are said to be feasible to run.